Case Study: In Situ Experimental Investigation on Overburden Consolidation Grouting for Columnar Jointed Basalt Dam Foundation. (24th February 2020) - Dou, Jinxi; Zhou, Mengxia; Wang, Zhilin; Wang, Kexiang; Yuan, Shui; Jiang, Mingqiang; Zhang, Guijin
Abstract : The dam foundation rock mass, at the Baihetan hydropower station on the Jinsha River, is mainly columnar jointed basalt, with faults and fissures developed. Considering adverse factors such as the unloading relaxation or the opening of the fissures due to excavation blasting, consolidation grouting is needed to improve the integrity of the dam foundation rock mass. According to the physical and mechanical properties of columnar jointed basalt and the continuity of construction, the effectiveness of overburden consolidation grouting is experimentally studied. The results show that this grouting technology can obviously improve the integrity and uniformity of a dam foundation rock mass and reduce the permeability of the rock mass. After grouting, the average increase in the wave velocity of the rock mass is 7.3%. The average improvement in the deformation modulus after grouting is 13.5%. After grouting, the permeability of 99% of the inspection holes in the Lugeon test section had Lugeon values of no more than 3 LU. This improvement is considerable and provides a case to engineering application.